2020
DOI: 10.3390/ijerph17155474
|View full text |Cite
|
Sign up to set email alerts
|

Balance Tests in Pre-Adolescent Children: Retest Reliability, Construct Validity, and Relative Ability

Abstract: Balance is an essential prerequisite for the normal physical development of a child. It consists of the ability to maintain the body’s centre of mass over its base of support, which is enabled by automatic postural adjustments, and maintain posture and stability in various conditions and activities. The present study aimed to determine the measurement characteristics (reliability and concurrent validity) and the relative ability of balance tests and different motor tests in healthy 11-year-olds. We also evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 62 publications
2
18
0
2
Order By: Relevance
“…Finally, girls performed better than boys in the balance beam test. These results are in line with previous studies that have shown better performance on balance tests in girl children and adolescent girls than boys [ 5 , 53 , 54 ]. This could be caused by the considerable disparities in pre-pubertal posture between boys and girls, since they have different body heights and weights, which result in different lumbar angles and centers of gravity [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, girls performed better than boys in the balance beam test. These results are in line with previous studies that have shown better performance on balance tests in girl children and adolescent girls than boys [ 5 , 53 , 54 ]. This could be caused by the considerable disparities in pre-pubertal posture between boys and girls, since they have different body heights and weights, which result in different lumbar angles and centers of gravity [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…The technical and compositional characteristics of these materials used can have major influences on physical capacity, perception of effort, body posture and vestibular and neuromotor rehabilitation. Consistent with the results of our study, previous studies have highlighted the influence of exercises performed on different fitness materials in order to improve static and dynamic balance [ 5 , 53 , 54 , 55 ]. The results of our study complete the research on the study of the up plank position, which were numerous and especially highlighted the anatomical, biomechanical and physical benefits of different categories of subjects actively involved in physical and sports activities [ 56 , 57 , 58 , 59 ], in the practice of fitness [ 55 , 60 , 61 , 62 , 63 ] and in prophylaxis [ 64 , 65 , 66 , 67 , 68 ].…”
Section: Discussionsupporting
confidence: 93%
“…The chair, with rubber tips on the legs, is placed against a wall to prevent it from moving. People with osteoarthritis 18 - 64 years Concurrent criterion validity Good test-retest reliabilityICC=0.87 Silva et al [ 31 ] single-leg stance (SLS) (SLS) Test is used to assess static postural and balance control.These protocols usually include eyes open and eyes closed test-variations Children with musculoskeletal birth defects such as Congenital talipes equinovarus 4 -18 years Construct Validity Excellent reliabilityICC= 0.81- 0.91 Sember et al [ 32 ] ABILOCO-kids Assessing the walking ability of children with CP focusing on the activity domain of the ICF Children with CP 6 - 15 years Construct validity Excellent reliabilityICC= 0.96 Gilles et al [ 33 ] 6-minute walk test (6MWT) Used to define their capacities and to evaluate therapeutic interventions. Children with CP 4 - 18 years Criterion Validity Excellent test-retestICC= 0.98 Fitzgerald et al [ 34 ] 28-item Mobility Questionnaire (Mob- Ques28) scores mobility limitations on a scale of 0 to 100 Children with CP 2 - 13 years Good validity Good reliabilityICC=0.87 Van Ravesteyn et al [ 35 ] ActiGraph GT3X+ The initialization is to record the number of steps and acceleration at a frequency of 100 Hz within 5 seconds.…”
Section: Resultsmentioning
confidence: 99%